Safe on the road – Does Advanced Driver-Assistance Systems Use affect Road Risk Perception?. (August 2020) - Hagl, Maria; Kouabenan, Dongo Rémi
Highlights: ADAS users feel safer on the road than drivers without ADAS. ADAS users perceive lower accident probability than drivers without ADAS. ADAS users perceive more control over road risks than drivers without ADAS. ADAS use can give false sense of control. Abstract: A major goal of advanced driver-assistance systems (ADAS) deployment is higher road safety. However, these systems are only as safe as users handle them. This article presents a study evaluating the links between the use of ADAS and road risk perception. 101 drivers were invited to evaluate accident probability and risk controllability and to indicate whether they were using ADAS or not. Results show that the use of ADAS decreases perceived accident probability and increases perceived controllability for risky driving situations. Since the degree of automation in ADAS is still low nowadays, it is important to discuss the importance of human factors for the purpose of a safer implementation.